Preparation method of quantum dot electroluminescent device with micro-nano pixels

By using PDMS embossed seals in quantum dot electroluminescent devices, the barrier layer is directly peeled off and filled with luminescent materials, the problems of low patterning quality and low electroluminescent efficiency are solved, and efficient micro-nano cell preparation and electroluminescent performance are achieved.

CN119907598APending Publication Date: 2025-04-29SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311358937.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, the barrier layer patterning quality is low, the large acupuncture between the display array cells, and the low electroluminescence efficiency caused by leakage current.

Method used

A method for preparing a quantum dot electroluminescent device with micro-nano cells is adopted, including spin-coating a hole injection layer, a hole transport layer, an interface layer, a barrier layer and annealing and drying treatment on the first electrode; then directly peeling the barrier layer with a PDMS stamp to form a patterned missing area, and filling the missing area with a luminescent material to form a micro-nano cell; finally spin-coating the electron transport layer and evaporating the second electrode.

Benefits of technology

The patterned barrier layer is directly formed through a single imprinting process, which reduces deformation and cracks caused by stress, improves patterning quality, reduces electrical crosstalk and leakage current between cells, and improves electroluminescent efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907598A_ABST
    Figure CN119907598A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a quantum dot electroluminescent device with micro-nano pixels, and belongs to the technical field of luminescent devices. The preparation method comprises the following steps: S1, sequentially spin-coating a hole injection layer, a hole transport layer, a vacuum gas phase deposition interface layer and a spin-coating barrier layer on a first electrode, and carrying out annealing and drying treatment; s2, adhering a pretreated PDMS convex seal to the barrier layer, enabling a convex part of the PDMS convex seal to be in complete contact with the barrier layer, carrying out annealing and drying treatment, and then moving away the PDMS convex seal to form a patterned missing region; s3, filling the patterned missing region with a luminescent material to form a micro-nano pixel; and S4, spin-coating an electron transport layer on the sample, annealing and drying, and evaporating a second electrode to obtain the device. According to the preparation method, the patterning quality of the barrier layer is improved, the electrical crosstalk between pixels is remarkably reduced, the electroluminescent efficiency loss caused by leakage current is inhibited, and the patterning quality of light-emitting quantum dots subsequently filled into the missing region of the barrier layer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of light-emitting devices, and in particular relates to a method for preparing a quantum dot electroluminescent device with micro-nano pixels. Background Art

[0002] Quantum dot electroluminescent devices with nano-pixel size have broad application prospects in "near-eye" devices, such as head-mounted displays and smart glasses for virtual reality (VR) and augmented reality (AR) applications. For commercial display devices based on electroluminescence, ultra-high resolution is the future development trend. Therefore, it is of great significance to prepare sub-micron-sized luminescent quantum dot pixels (quantum dot micro-nano pixels).

[0003] Nanoimprint technology is a contact transfer technology for nanomaterials. Due to its solvent-free process, it has shown great advantages in the field of quantum dot patterning and can realize submicron-sized luminescent quantum dot pixels (quantum dot micro-nano pixels).

[0004] The structure of ordinary quantum dot light-emitting diode (QLED) includes anode / hole injection layer / hole transport layer / quantum dot layer / electron transport layer / cathode. After voltage is applied, electrons and holes are injected from the corresponding electrodes, injected and transported to the light-emitting layer through various functional layers, and carriers in the quantum dots generate photons through radiation recombination; patterned QLED is further processed on the basis of ordinary QLED, and barrier layer materials are printed in two steps through nanoimprinting and other technologies, and quantum dots are coated, and the quantum dot layer is processed into quantum dot pixels arranged in an array with a fixed spacing. The smaller the size of the quantum dot pixel and the denser the arrangement, the higher the resolution of the patterned QLED.

[0005] The main process of the two-step imprinting technology includes picking up and printing, and a highly adhesive polydimethylsiloxane (PDMS) gravure stamp is used as a medium. First, the pre-prepared nanomaterials on the donor substrate are picked up onto the PDMS gravure stamp, and then the PDMS gravure stamp with nanomaterials is brought into contact with the receptor substrate. After the stamp is removed, the nanomaterials can be printed on the receptor substrate.

[0006] The existing technology for preparing quantum dot micro-nano pixels by nanoimprinting is to first prepare the PDMS gravure stamp corresponding to the required micro-nano pixels (micro-nano means that the maximum line width of the pixel is less than 1 micron); adhere the PDMS gravure stamp with the pixel pattern to the barrier layer material, so that there is no concave part of the PDMS gravure stamp that is completely in contact with the barrier layer material, and anneal and dry it; after annealing and drying, separate the PDMS stamp from the donor substrate, and the part in contact with the PDMS gravure stamp is completely peeled off, and the patterned barrier layer material is picked up on the PDMS gravure stamp; then adhere the PDMS gravure stamp that has picked up the patterned barrier layer material to the hole transport layer, so that the barrier layer material is completely in contact with the hole transport layer, and anneal and dry it. After annealing and drying, separate the PDMS gravure stamp from the receptor substrate, and the patterned barrier layer material is printed on the hole transport layer. However, it is a two-step embossing of the barrier layer material by the PDMS gravure stamp to coat the quantum dots. Multiple imprints and uneven stresses cause cracks in the barrier layer, distortion of the sidewalls, and uncontrollable changes in the pixel area, which affects the patterning quality and reduces the barrier effect. This ultimately leads to increased electrical crosstalk between pixels, increased leakage current, and reduced pixel electroluminescence efficiency. Summary of the invention

[0007] Therefore, the technical problem to be solved by the present invention is to overcome the problems in the prior art such as low patterning quality of the barrier layer, large crosstalk between pixels in the display array, and low electroluminescent efficiency caused by leakage current.

[0008] In order to solve the above technical problems, the present invention provides a method for preparing a quantum dot electroluminescent device with micro-nano pixels.

[0009] The object of the present invention is to provide a method for preparing a quantum dot electroluminescent device having micro-nano pixels, comprising the following steps:

[0010] S1, sequentially spin-coating a hole injection layer and a hole transport layer on the first electrode, vacuum vapor depositing an interface layer, spin-coating a barrier layer, and annealing and drying;

[0011] S2, adhering the pre-treated PDMS embossed stamp to the barrier layer described in S1, so that the raised portion of the PDMS embossed stamp is in full contact with the barrier layer and annealing and drying is performed, and then the PDMS embossed stamp is removed, and the contact portion between the barrier layer and the PDMS embossed stamp is completely peeled off, exposing the interface layer, and forming a patterned missing area;

[0012] S3, filling the patterned missing area described in S2 with a luminescent material to form a micro-nano pixel;

[0013] S4, spin coating an electron transport layer on the sample formed by S3, annealing and drying the layer, and evaporating a second electrode to obtain the quantum dot electroluminescent device with micro-nano pixels.

[0014] In one embodiment of the present invention, in S1, the material of the hole injection layer is selected from polyethylene polymers and / or polythiophene polymers; and the thickness of the hole injection layer is 10 nm-150 nm.

[0015] Furthermore, the polyethylene polymer is selected from poly(thiophene-3-[2-(2-methoxyethoxy)ethoxy]-2,5-diyl)( OC), poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), and one or more of a PEDOT:PSS modified material doped with a perfluoroionomer (PEDOT:PSS:PFI).

[0016] Furthermore, the polythiophene polymer is selected from PTT:PFFSA.

[0017] In one embodiment of the present invention, in S1, the material of the hole transport layer is selected from one or more of triphenylamine-based compounds and their derivative polymers, fluorene-based compounds and their derivative polymers, carbazole-based compounds and their derivative polymers, and spirocyclic compounds; the thickness of the hole transport layer is 10nm-150nm, and has good film-forming properties and hole mobility.

[0018] Furthermore, the triphenylamine compound and its derivative polymer are selected from one or more of 4,4',4"-tri(carbazole-9-yl)triphenylamine (TCTA), N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), 4,4,4"-tri[(2,3,4,5-tetraphenyl)phenyl]aniline (TTPPPA)Poly-TPD, and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA).

[0019] Furthermore, the fluorene-based compound and its derivative polymer are selected from one or more of N,N'-iminodiphenyl-4,4'-fluorene, 9,9-bis[4-(di-p-toluylamino)phenyl]-2,7-bis-(2-naphthylphenylamino)fluorene, and poly(9,9-dioctylfluorene-co-N-(4-(sec-butyl)phenyl)diphenylamine) (TFB).

[0020] Furthermore, the carbazole-based compound and its derivative polymer are selected from one or more of 4,4'-bis(9-carbazole)biphenyl (CBP), 3',6'-bis(carbazole-9-yl)-bis[9-(2-ethylhexyl)carbazole-3,6-diyl] (G1CBC), and polyvinylcarbazole (PVK).

[0021] Furthermore, the spirocyclic compound is selected from one or more of N,N'-bis(3-methylphenyl)-N,N'-di(phenyl)-2,7-diamino-9,9-spirobifluorene (Spiro-TPD) and 2,2',7,7'-tetrakis(N,N-diphenylamino)-2,7-diamino-9,9-spirophenanthrene (Spiro-TAD).

[0022] In one embodiment of the present invention, in S1, the material of the interface layer is selected from trichlorosilane compounds; the thickness of the interface layer is 1nm-5nm, the surface adhesion is low, and the thickness is thin; the interface layer can be a monolayer or multiple superimposed monolayers; the interface layer will not affect the hole transfer rate and will not cause a decrease in electroluminescence efficiency.

[0023] Furthermore, the trichlorosilane compound is selected from one or more of methyltrichlorosilane (TMCS), (tridecafluoro-1,1,2,2-tetrahydrooctyl)trichlorosilane (OTCS), and (heptadecafluoro-1,1,2,2-tetrahydrooctyl)trichlorosilane (DTCS).

[0024] In one embodiment of the present invention, in S1, the material of the barrier layer is selected from metal oxide nanocrystals; and the thickness of the barrier layer is 10 nm-100 nm.

[0025] Furthermore, the metal oxide nanocrystals are selected from nano-alumina (Al 2 O 3 ), nano silicon oxide (SiO 2 ), nano magnesium oxide (MgO), nano zirconium oxide (ZrO 2 ) and nano-yttrium oxide (Y 2 O 3 )

[0026] In one embodiment of the present invention, in S2, the height of the raised portion of the PDMS embossed stamp is 200nm-2μm, the minimum line width of the raised portion is 200nm-1μm, and the Young's modulus of the material of the PDMS embossed stamp is 5MPa-15MPa. The pattern of the raised portion of the PDMS embossed stamp is consistent with the pattern of the luminous pixel, reducing the distortion rate during the pattern transfer process.

[0027] In one embodiment of the present invention, in S2, the preparation of the PDMS embossed stamp comprises the following steps:

[0028] S21, spin coating a positive photoresist on the silicon wafer, and performing annealing and drying treatment;

[0029] S22, exposing the photoresist using electron beam lithography (EBL) technology, and developing the photoresist;

[0030] S23, etching the exposed silicon wafer by plasma etching technology, and performing ultrasonic treatment to remove residual photoresist;

[0031] S24, pour PDMS prepolymer onto the template with a thickness of 5mm-15mm, separate the PDMS from the silicon master after curing, and obtain the PDMS embossed stamp.

[0032] In one embodiment of the present invention, in S2, the pretreatment method is selected from ultraviolet ozone treatment and / or oxygen plasma treatment, which can enhance the adhesion between the PDMS embossed stamp and the barrier layer, and promote the complete peeling of the contact part between the barrier layer and the PDMS embossed stamp.

[0033] In one embodiment of the present invention, in S3, the light-emitting material is selected from II-VI quantum dot (nanocrystalline) material, III-V quantum dot (nanocrystalline) material, perovskite semiconductor material or single-mass quantum dot (nanocrystalline) material.

[0034] Furthermore, the II-VI quantum dot (nanocrystalline) material is selected from one or more of cadmium-based quantum dots (cadmium selenide, cadmium sulfide), zinc-based quantum dots (zinc selenide, zinc telluride), and zinc-cadmium-based alloy quantum dots (ZnCdSeS).

[0035] Furthermore, the III-V quantum dot (nanocrystalline) material is selected from indium-based quantum dots (indium phosphide, indium arsenide).

[0036] Furthermore, the perovskite semiconductor material is selected from quantum dot (nanocrystalline) materials or bulk materials such as cesium bromide, cesium bromide-chloride, methylamine bromide, and methylamidinium iodide.

[0037] Furthermore, the single-mass quantum dot material is selected from one or both of carbon quantum dots (nanocrystals) and silicon quantum dots (nanocrystals).

[0038] In one embodiment of the present invention, in S3, the micro-nano pixel is formed by stacking many spherical colloidal quantum dots (nanocrystals), and the spherical colloidal quantum dots are filled in the array of the missing area to form a pattern complementary to the barrier layer; the spherical colloidal quantum dots (nanocrystals) have fluorescent properties, and all spherical colloidal quantum dots (nanocrystals) in the micro-nano pixel have the same chemical composition.

[0039] In one embodiment of the present invention, in S4, the material of the electron transport layer is selected from one or more of metal oxides, imidazole compounds, pyridine compounds, pyrimidine compounds, anthracene compounds, organic metal chelates and compounds containing o-phenanthroline groups; the thickness of the electron transport layer is 10nm-150nm, and has good electron mobility and electron injection performance.

[0040] Furthermore, the metal oxide is selected from tin oxide (SnO 2 ), zinc oxide (ZnO) and zinc magnesium oxide (Zn 1- x Mg x O) in one or more.

[0041] Furthermore, the imidazole compound is selected from 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) and / or 1,3,5-tris(2-(pyridin-2-yl)-1H-benzo[d]imidazol-1-yl)benzene (iTPyBIB).

[0042] Furthermore, the pyridine compound is selected from 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene (TmPyPB) and / or 1,3,5-tris(4-pyridin-3-ylphenyl)benzene (TpPyPB).

[0043] Furthermore, the pyrimidine compound is selected from 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM) and / or 4,6-bis(3,5-di(4-pyridyl)phenyl)-2-methylpyrimidine (B4PYMPM).

[0044] Furthermore, the anthracene compound is selected from 9,10-bis(6-phenylpyridin-3-yl)anthracene (DPPyA).

[0045] Furthermore, the organic metal chelate is selected from tris(8-hydroxyquinoline)aluminum (Alq3).

[0046] Furthermore, the compound containing o-phenanthroline group is selected from 4,7-diphenyl-1,10-phenanthroline (BPhen) and / or 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).

[0047] In one embodiment of the present invention, the materials of the first electrode and the second electrode are independently selected from one or more of indium tin oxide (ITO), fluorine-doped tin dioxide (FTO), aluminum (Al) and silver (Ag); the thickness of the first electrode and the second electrode are independently 20nm-200nm, have good conductivity, and can transmit charges.

[0048] In one embodiment of the present invention, the quantum dot electroluminescent device having micro-nano pixels further includes a substrate.

[0049] In one embodiment of the present invention, the material of the substrate is selected from one or more of glass, polyethylene terephthalate (PET) and mica, and the substrate has good interface properties.

[0050] The technical solution of the present invention has the following advantages over the prior art:

[0051] (1) The preparation method described in the present invention directly peels off the barrier layer through nanoimprint technology to form a patterned missing area, and then coats the luminescent material in the patterned missing area to form a micro-nano pixel. Only one imprint process is required, and no uneven stress is introduced. Compared with the secondary imprinting in the prior art, the process difficulty is reduced. Moreover, the patterned barrier layer prepared by this method does not undergo the picking and printing in the secondary imprinting in the prior art, no external pressure is applied, and there is no deformation caused by stress, which improves the patterning quality of the barrier layer, significantly reduces the electrical crosstalk between pixels, suppresses the loss of electroluminescent efficiency caused by leakage current, and improves the patterning quality of the luminescent quantum dots that are subsequently filled in the missing area of ​​the barrier layer.

[0052] (2) The preparation method described in the present invention adds an interface layer between the hole transport layer and the barrier layer. The surface of the interface layer has a straight carbon chain structure. Low adhesion is an intrinsic property of the interface layer material. The adhesion between the barrier layer and the interface layer is low, which enables the area defined by the contact part between the barrier layer and the PDMS embossed stamp to be completely peeled off.

[0053] (3) The preparation method described in the present invention performs ultraviolet ozone treatment or oxygen plasma treatment on the PDMS embossed stamp. The ultraviolet ozone treatment or oxygen plasma treatment can increase the free charge on the surface of the PDMS embossed stamp, thereby increasing the adhesion of the PDMS embossed stamp and promoting the complete peeling of the area defined by the contact portion between the barrier layer and the PDMS embossed stamp. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0055] Figure 1 It is a cross-sectional schematic diagram of a quantum dot electroluminescent device with micro-nano pixels of the present invention;

[0056] Figure 2 The process flow chart of the quantum dot electroluminescent device with micro-nano pixels of the present invention;

[0057] Figure 3 is a schematic diagram of a barrier layer of the present invention;

[0058] Figure 4 is a top view of the barrier layer of the present invention;

[0059] Figure 5 It is a process flow chart of the PDMS embossed stamp of the present invention;

[0060] Figure 6It is a scanning microscope image of a sample of the present invention that is not coated with a luminescent material; wherein the left image is Example 1, and the right image is Comparative Example 1;

[0061] Figure 7 The scanning microscope images of the samples of the present invention not coated with the luminescent material; wherein the left image is Example 1, and the right image is Comparative Example 2;

[0062] Figure 8 It is an optical microscope picture of a pixel in the light-emitting state of the quantum dot electroluminescent device of the present invention; wherein the left picture is Example 1, and the right picture is Comparative Example 1;

[0063] Fig. 9 The normalized current density and voltage curve of the quantum dot electroluminescent device of the present invention in the luminescent state;

[0064] Fig.10 It is a normalized external quantum efficiency and brightness curve of the quantum dot electroluminescent device of the present invention in the light-emitting state;

[0065] Explanation of the accompanying drawings: 1-substrate, 2-first electrode, 3-hole injection layer, 4-hole transport layer, 5-interface layer, 6-barrier layer, 7-micro-nano pixel, 8-electron transport layer, 9-second electrode. DETAILED DESCRIPTION

[0066] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0067] In the present invention, unless otherwise specified, the ITO substrate used in the embodiments includes a glass substrate 1 and an ITO first electrode 2 .

[0068] In the present invention, unless otherwise specified, the PEDOT:PSS used in the examples is purchased from J&K, model number 4083.

[0069] In the present invention, unless otherwise specified, the TFB used in the examples is purchased from Lumtec, Taiwan, China, with a model number of LT-N148.

[0070] In the present invention, unless otherwise specified, the PVK used in the examples was purchased from Sigma-Aldrich, model number 25067-69-8.

[0071] In the present invention, unless otherwise specified, the PDMS prepolymer used in the examples is purchased from Suzhou Guangdi Co., Ltd. and has a Young's modulus of 5 MPa-15 MPa.

[0072] Example 1

[0073] Reference Figure 1-5As shown, the quantum dot electroluminescent device with micro-nano pixel of the present invention (using a one-time imprinting process) has a minimum pixel of 500nm, a central wavelength of 630nm, TMCS as the interface layer, and Al 2 O 3 The nanocrystal is a barrier layer, and the cadmium selenide quantum dots (nanocrystals) are luminescent materials. The preparation thereof specifically includes the following steps:

[0074] (1) Preparation of PDMS embossed stamp

[0075] S1. Spin-coat a positive photoresist (PMMAA4) on a clean silicon wafer, and anneal and dry it;

[0076] S2, using electron beam lithography (EBL) to expose the photoresist and perform development processing;

[0077] S3, etching the exposed silicon wafer by plasma etching technology, and removing the residual photoresist by ultrasonication in acetone and isopropanol solution;

[0078] S4, PDMS prepolymer mixture was poured onto the template with a thickness of 5 mm and then cured at room temperature for 24 h;

[0079] S5. Separate the PDMS from the silicon master to obtain a PDMS embossed stamp with a pattern; the height of the convex portion of the PDMS embossed stamp is 800 nm, and the pattern is a circular honeycomb array with a diameter of 500 nm.

[0080] (2) Preparation of quantum dot electroluminescent devices with micro-nano pixels

[0081] S1. Use glass cleaning liquid, deionized water, acetone and isopropanol to ultrasonically clean the ITO substrate in sequence, and then put the cleaned ITO substrate into a UV ozone cleaning machine for 15 minutes of pretreatment;

[0082] S2, using a coating machine to spin coat the hole injection layer material PEDOT:PSS on the ITO substrate at a rate of 5000 r / min, and then annealing at 150° C. to form a hole injection layer 3 with a thickness of about 150 nm;

[0083] S3, transferring the substrate to a glove box in a nitrogen atmosphere, using a coating machine to spin-coat the hole transport layer material TFB on the sample formed in S2 at a rate of 3000 r / min, and then annealing at 150° C. to form a hole transport layer 4 with a thickness of about 50 nm;

[0084] S4, take 20 μL of TMCS interface layer solution in a beaker, put the sample formed by S3 and the beaker containing the TMCS interface layer solution into a vacuum dryer, use a mechanical pump to reduce the vacuum degree to 0.1 MPa, turn off the mechanical pump, and maintain the vacuum degree at 0.1 MPa; the TMCS interface layer solution is vaporized into gas, and finally deposited on the sample formed by S3, and the vacuum vapor deposition time is controlled; after the deposition is completed, the vacuum dryer is restored to standard atmospheric pressure, the sample is taken out and annealed at 70° C. to form an interface layer 5 with a thickness of about 2 nm;

[0085] S5. Use a glue machine to coat the barrier layer material Al 2 O 3 The nanocrystals were spin-coated on the sample formed by S4 at a rate of 5000 r / min, and then annealed at 70°C to form a barrier layer 6 with a thickness of about 50 nm;

[0086] S6. The prepared PDMS stamp was pretreated in a UV-ozone cleaning machine for 15 min. The PDMS stamp was bonded to the sample formed in S5. A nanoimprinter was used to apply a pressure of 1.5 bar at 70 °C for 1 min, and then the pressure was removed to separate the PDMS stamp from the sample. 2 O 3 The contact portion of the barrier layer 6 with the PDMS embossed stamp is completely peeled off, exposing the underlying interface layer 5, forming a patterned missing region;

[0087] S7, using a coating machine to spin-coat the luminescent material cadmium selenide quantum dots (nanocrystals) on the sample formed by S6 at a rate of 2000 r / min, and the cadmium selenide quantum dots (nanocrystals) are filled in the missing areas of the patterned barrier layer to form micro-nano pixel 7;

[0088] S8, using a coating machine to spin-coat the electron transport layer material ZnO nanocrystals on the sample formed in S7 at a rate of 2000 r / min, and then annealing at 80° C. to form an electron transport layer 8 with a thickness of about 100 nm;

[0089] S9, transferring to a vacuum evaporation device to physically vapor deposit silver, a second electrode material, on the sample formed in S8 to form a second electrode 9 with a thickness of about 100 nm;

[0090] The final device structure is ITO / PEDOT:PSS / TFB / TMCS / micro-nano pixel: cadmium selenide quantum dot (nanocrystalline) pixel and Al 2 O 3 Complementary pattern structure formed by barrier layer / ZnO / Ag.

[0091] Example 2

[0092] Reference Figure 1-5 As shown, the quantum dot electroluminescent device with micro-nano pixel of the present invention (using a one-time imprinting process) has a minimum pixel of 800nm, a central wavelength of 525nm, OTCS as the interface layer, and SiO 2 The nanocrystal is a barrier layer, and the cesium lead bromide perovskite quantum dots (nanocrystals) are a luminescent material. The preparation thereof specifically includes the following steps:

[0093] (1) Preparation of PDMS embossed stamp

[0094] S1. Spin-coat a positive photoresist (PMMAA4) on a clean silicon wafer, and anneal and dry it;

[0095] S2, using electron beam lithography (EBL) to expose the photoresist and perform development processing;

[0096] S3, etching the exposed silicon wafer by plasma etching technology, and removing the residual photoresist by ultrasonication in acetone and isopropanol solution;

[0097] S4, PDMS prepolymer mixture was poured onto the template with a thickness of 5 mm and then cured at room temperature for 24 h;

[0098] S5. Separate the PDMS from the silicon master to obtain a PDMS embossed stamp with a pattern; the height of the convex portion of the PDMS embossed stamp is 1 μm, and the pattern is a circular honeycomb array with a diameter of 800 nm.

[0099] (2) Preparation of quantum dot electroluminescent devices with micro-nano pixels

[0100] S1. Use glass cleaning liquid, deionized water, acetone and isopropanol to ultrasonically clean the ITO substrate in sequence, and then put the cleaned ITO substrate into a UV ozone cleaning machine for 15 minutes of pretreatment;

[0101] S2, using a coating machine to spin coat the hole injection layer material PTT:PFFSA on the ITO substrate at a rate of 5000 r / min, and then annealing at 150° C. to form a hole injection layer 3 with a thickness of about 150 nm;

[0102] S3, transferring the substrate to a glove box in a nitrogen atmosphere, using a coating machine to spin coat the hole transport layer material PVK on the sample formed in S2 at a rate of 3000 r / min, and then annealing at 150° C. to form a hole transport layer 4 with a thickness of about 50 nm;

[0103] S4, take 20 μL of OTCS interface layer solution in a beaker, put the sample formed by S3 and the beaker containing the OTCS interface layer solution into a vacuum dryer, use a mechanical pump to reduce the vacuum degree to 0.1 MPa, turn off the mechanical pump, and maintain the vacuum degree at 0.1 MPa; the OTCS interface layer solution is vaporized into gas, and finally deposited on the sample formed by S3, and the vacuum vapor deposition time is controlled; after the deposition is completed, the vacuum dryer is restored to standard atmospheric pressure, the sample is taken out and annealed at 70° C. to form an interface layer 5 with a thickness of about 2 nm;

[0104] S5. Use a glue machine to coat the barrier layer material SiO 2 The nanocrystals were spin-coated on the sample formed by S4 at a rate of 5000 r / min, and then annealed at 70°C to form a barrier layer 6 with a thickness of about 50 nm;

[0105] S6: The prepared PDMS stamp was pretreated in a UV-ozone cleaning machine for 15 min, and the PDMS stamp was bonded to the sample formed in S5. A nanoimprinter was used to apply a pressure of 1.5 bar at 70 °C for 1 min, and then the pressure was removed to separate the PDMS stamp from the sample. 2 The contact portion of the barrier layer 6 with the PDMS embossed stamp is completely peeled off, exposing the underlying interface layer 5, forming a patterned missing region;

[0106] S7, using a coating machine to spin-coat the luminescent material cesium lead bromine perovskite quantum dots (nanocrystals) on the sample formed by S6 at a rate of 2000 r / min, and the cesium lead bromine perovskite quantum dots (nanocrystals) are filled in the missing areas of the patterned barrier layer to form micro-nano pixel 7;

[0107] S8, transferring the sample formed in S7 to a vacuum evaporation device to physically vapor deposit an electron transport layer material TPBi to form an electron transport layer 8 with a thickness of about 100 nm;

[0108] S9, continue to vapor-deposit 5 nm of lithium fluoride (LiF), a second electrode modification layer, on the sample formed by S8; transfer to a vacuum evaporation device to physically vapor-deposit aluminum, a second electrode material, to form a second electrode 9 with a thickness of about 100 nm;

[0109] The final device structure is ITO / PTT:PFFSA / PVK / OTCS / micro-nano pixel: cesium lead bromide perovskite quantum dot (nanocrystalline) pixel and SiO 2 Complementary pattern structure formed by barrier layer / TPBi / LiF / Al.

[0110] Comparative Example 1 is basically the same as Example 1, except that: a secondary embossing process is used, and there is no interface layer.

[0111] Quantum dot electroluminescent device with micro-nano pixels, the smallest pixel is 500nm, the central wavelength is 630nm, Al 2 O 3 The nanocrystal is a barrier layer, and the cadmium selenide quantum dots (nanocrystals) are luminescent materials. The preparation thereof specifically includes the following steps:

[0112] (1) Preparation of PDMS gravure stamp

[0113] S1. Spin-coat a negative photoresist (model RC600C) on a cleaned silicon wafer, and anneal and dry it;

[0114] S2, using electron beam lithography (EBL) to expose the photoresist and perform development processing;

[0115] S3, etching the exposed silicon wafer by plasma etching technology, and soaking it in HF:BOE buffer (HF:BOE buffer = 7 / 1) for 1 min to remove residual photoresist;

[0116] S4, PDMS prepolymer mixture was poured onto the template with a thickness of 5 mm and then cured at room temperature for 24 h;

[0117] S5. Separate the PDMS from the silicon master to obtain a PDMS gravure stamp with a pattern; the depth of the concave portion of the PDMS gravure stamp is 800 nm, and the pattern is a circular honeycomb array with a diameter of 500 nm.

[0118] (2) Preparation of quantum dot electroluminescent devices with micro-nano pixels

[0119] S1. Use glass cleaning liquid, deionized water, acetone and isopropanol to ultrasonically clean the ITO substrate in sequence, and then put the cleaned ITO substrate into a UV ozone cleaning machine for 15 minutes of pretreatment;

[0120] S2, using a coating machine to spin coat the hole injection layer material PEDOT:PSS on the ITO substrate at a rate of 5000 r / min, and then annealing at 150° C. to form a hole injection layer with a thickness of about 150 nm;

[0121] S3, the substrate was transferred to a glove box with a nitrogen atmosphere, and a hole transport layer material TFB was spin-coated on the sample formed in S2 at a rate of 3000 r / min using a coating machine, and then annealed at 150° C. to form a hole transport layer with a thickness of about 50 nm;

[0122] S4. Use a glue machine to coat the barrier layer material Al 2 O 3The nanocrystals were spin-coated on a silicon wafer at a rate of 5000 r / min and then annealed at 70°C to form a barrier layer with a thickness of about 50 nm.

[0123] S5, attaching the PDMS gravure stamp to the sample formed by S4, applying a pressure of 1.5 bar at 70° C. using a nanoimprint machine, and removing the pressure after 1 min, separating the PDMS gravure stamp from the sample formed by S4, and picking up the patterned barrier layer onto the PDMS gravure stamp, wherein the pattern is the same as the complementary part of the concave area of ​​the PDMS gravure stamp;

[0124] S6, attaching the PDMS gravure stamp that picked up the patterned barrier layer to the sample formed by S4, applying a pressure of 1.5 bar at 70° C. using a nanoimprinter, and removing the pressure after 1 min, separating the PDMS gravure stamp from the sample, and printing the patterned barrier layer onto the sample formed by S4 to form a patterned missing area;

[0125] S7, using a coating machine to spin-coat the luminescent material cadmium selenide quantum dots (nanocrystals) on the sample formed by S6 at a rate of 2000 r / min, and the cadmium selenide quantum dots (nanocrystals) are filled in the missing areas of the patterned barrier layer to form micro-nano pixels;

[0126] S8, using a coating machine to spin-coat the electron transport layer material ZnO nanocrystals on the sample formed in S7 at a rate of 2000 r / min, and then annealing at 80° C. to form an electron transport layer with a thickness of about 100 nm;

[0127] S9, transferring to a vacuum evaporation device to physically vapor deposit silver, a second electrode material, on the sample formed in S8 to form a second electrode with a thickness of about 100 nm;

[0128] The final device structure is ITO / PEDOT:PSS / TFB / micro-nano pixel: cadmium selenide quantum dot (nanocrystalline) pixel and Al 2 O 3 Complementary pattern structure formed by barrier layer / ZnO / Ag.

[0129] Comparative Example 2 is basically the same as Example 1, except that: there is no interface layer

[0130] Quantum dot electroluminescent device with micro-nano pixels, the smallest pixel is 500nm, the central wavelength is 630nm, Al 2 O 3 The nanocrystal is a barrier layer, and the cadmium selenide quantum dots (nanocrystals) are luminescent materials. The preparation thereof specifically includes the following steps:

[0131] (1) Preparation of PDMS embossed stamp

[0132] S1. Spin-coat a positive photoresist (PMMAA4) on a clean silicon wafer, and anneal and dry it;

[0133] S2, using electron beam lithography (EBL) to expose the photoresist and perform development processing;

[0134] S3, etching the exposed silicon wafer by plasma etching technology, and removing the residual photoresist by ultrasonication in acetone and isopropanol solution;

[0135] S4, PDMS prepolymer mixture was poured onto the template with a thickness of 5 mm and then cured at room temperature for 24 h;

[0136] S5. Separate the PDMS from the silicon master to obtain a PDMS embossed stamp with a pattern; the height of the convex portion of the PDMS embossed stamp is 800 nm, and the pattern is a circular honeycomb array with a diameter of 500 nm.

[0137] (2) Preparation of quantum dot electroluminescent devices with micro-nano pixels

[0138] S1. Use glass cleaning liquid, deionized water, acetone and isopropanol to ultrasonically clean the ITO substrate in sequence, and then put the cleaned ITO substrate into a UV ozone cleaning machine for 15 minutes of pretreatment;

[0139] S2, using a coating machine to spin coat the hole injection layer material PEDOT:PSS on the ITO substrate at a rate of 5000 r / min, and then annealing at 150° C. to form a hole injection layer with a thickness of about 150 nm;

[0140] S3, the substrate was transferred to a glove box with a nitrogen atmosphere, and a hole transport layer material TFB was spin-coated on the sample formed in S2 at a rate of 3000 r / min using a coating machine, and then annealed at 150° C. to form a hole transport layer with a thickness of about 50 nm;

[0141] S4. Use a glue machine to coat the barrier layer material Al 2 O 3 The nanocrystals were spin-coated on the sample formed by S3 at a rate of 5000 r / min, and then annealed at 70 °C to form a barrier layer with a thickness of about 50 nm;

[0142] S5. The prepared PDMS embossed stamp was pretreated in a UV-ozone cleaning machine for 15 min. The PDMS embossed stamp was bonded to the sample formed in S4. A nanoimprinter was used to apply a pressure of 1.5 bar at 70 °C for 1 min, and then the pressure was removed to separate the PDMS embossed stamp from the sample. 2 O 3The contact part between the barrier layer and the PDMS embossed stamp was not completely peeled off, and there was a lot of barrier layer residue;

[0143] S6, using a coating machine to spin-coat the luminescent material cadmium selenide quantum dots (nanocrystals) on the sample formed by S5 at a rate of 2000 r / min, and the cadmium selenide quantum dots (nanocrystals) are filled in the missing areas of the patterned barrier layer to form micro-nano pixels;

[0144] S7, using a coating machine to spin-coat the electron transport layer material ZnO nanocrystals on the sample formed by S6 at a rate of 2000 r / min, and then annealing at 80° C. to form an electron transport layer with a thickness of about 100 nm;

[0145] S8, transferring to a vacuum evaporation device to physically vapor deposit silver, a second electrode material, on the sample formed in S7 to form a second electrode with a thickness of about 100 nm;

[0146] The final device structure is ITO / PEDOT:PSS / TFB / micro-nano pixel: cadmium selenide quantum dot (nanocrystalline) pixel and Al 2 O 3 Complementary pattern structure formed by barrier layer / ZnO / Ag.

[0147] Test Example 1

[0148] Based on Example 1 and Comparative Examples 1-2, samples that were not coated with luminescent materials or other subsequent steps were placed in a Sigma 300 scanning electron microscope to obtain Figure 6-7 Microscopic topographic image of the patterned barrier layer shown.

[0149] from Figure 6 It can be seen that because the patterned barrier layer of the first imprint does not undergo the picking up and printing in the second imprinting in the prior art, no external pressure is applied, and there is no deformation caused by stress, which reduces the number of cracks on the patterned barrier layer. Compared with the second imprinting transfer barrier layer of Comparative Example 1, the first imprinting of Example 1 directly picks up the barrier layer and coats the micro-nano pixel process, the pattern barrier layer has higher pattern accuracy and fewer cracks.

[0150] from Figure 7 It can be seen that because there is no interface layer material in Comparative Example 2, the barrier layer material cannot be completely stripped off, and part of the barrier layer material remains in the pixel area, blocking charge transfer. Compared with the barrier layer directly picked up by one imprint and coated with the micro-nano pixel process (with the interface layer) in Comparative Example 2 (without the interface layer), the barrier layer is more completely stripped off and the charge transfer is improved.

[0151] Test Example 2

[0152] The devices prepared in Example 1 and Comparative Example 1 were placed in a test fixture, and a Keithley 2400 source meter was used to output voltage and observed under an optical microscope. Figure 8 The electroluminescent quantum dot micro-nano pixel image shown. Figure 8 It can be seen that because the patterned barrier layer of the first embossing does not undergo the picking up and printing in the second embossing in the prior art, no external pressure is applied, and there is no deformation caused by stress, which reduces the number of cracks on the patterned barrier layer, resulting in an increase in the precision of the pixel prepared by coating. Compared with the second embossing transfer barrier layer and the micro-nano pixel coating process of Comparative Example 1, the luminous pixel morphology is clearer and the brightness is more uniform.

[0153] Test Example 3

[0154] The devices prepared in Example 1 and Comparative Example 1 were placed in a test fixture with a silicon tube, and a Keithley 2400 source meter was used to output the voltage and record the current density. The picoammeter Keithley 6485 was used to measure the silicon tube response current, and the corresponding normalized current density ( Fig. 9 ), normalized external quantum efficiency EQE( Fig.10 ).from Figure 9-10 It can be seen that because the patterned barrier layer of the first imprint does not undergo the picking and printing in the second imprint in the prior art, no external pressure is applied, and there is no deformation caused by stress, which reduces the number of cracks on the patterned barrier layer. The patterned barrier layer in Example 1 has fewer cracks than the patterned barrier layer in Comparative Example 1, which reduces the leakage current caused by the cracks, increases the current efficiency at the same voltage, and improves the external quantum efficiency at the same brightness.

[0155] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a quantum dot electroluminescent device having micro-nano pixels, characterized in that: The following steps are included: S1, sequentially spin-coating a hole injection layer and a hole transport layer on the first electrode, vacuum vapor depositing an interface layer, spin-coating a barrier layer, and annealing and drying; S2, adhering the pre-treated PDMS embossed stamp to the barrier layer described in S1, so that the raised portion of the PDMS embossed stamp is in full contact with the barrier layer and annealing and drying is performed, and then the PDMS embossed stamp is removed, and the contact portion between the barrier layer and the PDMS embossed stamp is completely peeled off, exposing the interface layer, and forming a patterned missing area; S3, filling the patterned missing area described in S2 with a luminescent material to form a micro-nano pixel; S4, spin coating an electron transport layer on the sample formed by S3, annealing and drying the layer, and evaporating a second electrode to obtain the quantum dot electroluminescent device with micro-nano pixels.

2. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S1, the material of the hole injection layer is selected from polyethylene polymers and / or polythiophene polymers; and the thickness of the hole injection layer is 10 nm-150 nm.

3. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S1, the material of the hole transport layer is selected from one or more of triphenylamine-based compounds and their derivative polymers, fluorene-based compounds and their derivative polymers, carbazole-based compounds and their derivative polymers, and spirocyclic compounds; the thickness of the hole transport layer is 10nm-150nm.

4. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S1, the material of the interface layer is selected from trichlorosilane compounds; and the thickness of the interface layer is 1 nm-5 nm.

5. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S1, the material of the barrier layer is selected from metal oxide nanocrystals; and the thickness of the barrier layer is 10nm-100nm.

6. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S2, the height of the raised portion of the PDMS embossed stamp is 200 nm-2 μm, and the minimum line width of the raised portion is 200 nm-1 μm; the Young's modulus of the material of the PDMS embossed stamp is 5 MPa-15 MPa.

7. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S2, the pretreatment method is selected from ultraviolet ozone treatment and / or oxygen plasma treatment.

8. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S3, the light-emitting material is selected from II-VI quantum dot materials, III-V quantum dot materials, perovskite semiconductor materials or single-mass quantum dot materials.

9. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: In S4, the material of the electron transport layer is selected from one or more of metal oxides, imidazole compounds, pyridine compounds, pyrimidine compounds, anthracene compounds, organic metal chelates and compounds containing o-phenanthroline groups; the thickness of the electron transport layer is 10nm-150nm.

10. The method for preparing a quantum dot electroluminescent device having micro-nano pixels according to claim 1, characterized in that: The materials of the first electrode and the second electrode are independently selected from one or more of indium tin oxide, fluorine-doped tin dioxide, aluminum and silver; the thicknesses of the first electrode and the second electrode are independently 20nm-200nm.